Earthquake Risk Management for Mini-Hydro Power Plant: A Case Study Approach - Hafit Isandono; Aep Saepul Uyun; Andy Tirta; Erkata Yandri; Syukri Muhammad Nur (Journal of Renewable Energy, Electrical, and Computer Engineering, 2025)
This study evaluates the impact of an earthquake on a mini-hydropower plant (MHP) and formulates a disaster management strategy to enhance the operational resilience of MHPs against seismic events. Data was collected through interviews with relevant stakeholders, direct observations, and analysis of pertinent documents. The findings indicate that the 2018 Lombok earthquake caused severe damage to the catchment area, triggering increased sedimentation that disrupted the MHPs operation, resulting in decreased electricity production and escalated operational costs. Mitigation measures were implemented and proved effective in reducing debris-related downtime and improving electricity generation. Thes findings are expected to provide guidance for MHP operators in mitigating the negative impacts of earthquakes and similar disasters on plant operations.